VTAMN - A Smart Clothe for Ambulatory Remote Monitoring of Physiological Parameters and Activity - Noury, N.; Dittmar, A.; Corroy, C.; Baghai, R.; Weber, J.L.; Blanc, D.; Klefstat, F.; Blinovska, A.; Vaysse, S.; Comet, B. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2004)
The prototype of a communicating underclothe for medical remote monitoring was realized. It delivers physiological information on the subject (Cardiac Frequency, Breathing Frequency, surface and mid-temperature) as well as the environment and activity parameters (ambient temperature, fall detection). It also enables the automatic data transfer on event, with the localization of the subject.